Estudo da aderência no reparo com concreto autoadensável (CAA): influência do preparo da superfície, da resistência à compressão do concreto da base e do tipo do concreto (convencional e CAA) - Rocha, Adilson Pereira da (2011)
Efficient repairs in concrete structures require perfect bonding between the base concrete and the applied concrete. The experimental analysis shown in this study focused on how bonding is influenced by three types of base concrete preparation: hydro-jet blasting (BHD), manual scabbling (BMA) and mechanical scabbling (BME), as well as two types of base surface condition: dry (0%) and humid (100%) and also by the application of three different types of bonding agents: B - cement + water; C – cement + water + additive superplasticizer; D – cement + water + additive superplasticizer + active sílica. Fifteen conventional concrete bases prepared using concrete with compressive strength of class C20 and fifteen self-consolidating concrete bases with compressive strength of class C30 were tested. Surface roughness was characterized using profiles according to parameters Ra (standard deviation with respect to an average line) and Rz (average height between consecutives peaks and valleys). Self-consolidating concrete with C40 compressive strength was used to repair the concrete bases. Dyna Proceq apparatus was used to determine tension bonding strength. The hydro-jet blasting (BHD) preparation presented the lowest surface roughness values and the highest bonding strength results as well as the lowest values of the coefficient of variation. The manual scabbling (BMA) preparation presented intermediary results. The mechanical scabbling (BME) preparation presented the highest surface roughness values and the lowest bonding strength results. Surface humidity increase the number of concrete base ruptures. The use of bonding agents increased bonding strength regardless of the degree of surface humidity.